Uterine Arterial Pseudoaneurysm: Transcatheter Arterial Embolization as a Rare Complication of Caesarean Section - Ozdemir, Huseyin; Ozturk, Tulin; Kocakoc, Ercan; Kayali, Alperen (Lippincott Williams & Wilkins, 2009)
We describe the case of a 22-year-old female who presented to the emergency department with vaginal bleeding after Caesarean section. A diagnosis of pseudoaneurysm of the uterine artery was established radiologically. Pseudoaneurysm of the uterine artery is an uncommon cause of delayed postpartum hemorrhage. This condition can be treated with embolization.
Keywords: coil embolization; pseudoaneurysm; uterine artery